PENGARUH PENAMBAHAN ALKANOLAMIDA TERHADAP SIFAT-SIFAT UJI TARIK VULKANISAT KARET ALAM BERPENGISI KAOLIN - Yudha Widyanata, Indah M.S. Sitorus, Indra Surya (Jurnal Teknik Kimia USU, 2013)
By using a semi-efficient vulcanization system, Alkanolamide (ALK) was incorporated into kaolin-filled natural rubber compound at 1.0; 3.0; 5.0 and 7.0 parts per hundred rubber (phr). An investigation was carried out to examine the effect of ALK on tensile properties of the kaolin filled-natural rubber compound. It was found that ALK exhibited higher tensile modulus, tensile strength, and elongation at break up to 5.0 phr of ALK loading and then decreased with further increasing of ALK loading. Crosslink density measurement proved that 5.0 phr loading of ALK in the kaolin-filled natural rubber system exhibited greatest tensile properties due to its highest crosslink density formation.